Alberto Hidalgo in peruvian literature: From the avant-garde to the national expression - Pantigoso Pecero, Manuel (2018)
This essay, dedicated to the Arequipean poet Alberto Hidalgo, invite us to think over the work of this remarkable pioneer of avant-garde, who took Peru as an axis of its creative Verb. In a panoramic vision, we will see in which way his poetry has evolved from several angles: simplism, egocentrism and national expression. In addition, we account the characteristics of the avant-garde and its correlative distinctness with the current poetry. Finally, we gather various scholars’ comments of this Arequipean poet who is undoubtedly a controversial but fundamental one within our literary process.